Pengaruh Konseling Kognitif Perilaku Dengan Teknik Keterampilan Sosial Dan Teknik Pemecahan Masalah Terhadap Self Afiliasi - Wicaksani, Luh Widi; Suranata, Kadek; Dharsana, Ketut (Universitas Pendidikan Ganesha, 2018)
This study was aimed to understand: The effect of behavioral cognitive counseling by using social skill technique and problem-solving technique toward self-affiliation of the students. This study was â€œquasi-experimental researchâ€. The experimental design used was the Non-equivalent Pre-test Post-test Control Group Design. The population of this study was the grade X students of SMA Negeri 4 Singaraja which amounted to 395 people. This study used the intact group. The self-affiliation data collection of the students in this study used the self-affiliation questionnaire. Self-affiliation questionnaire had been tested for their validity and reliability. The analysis of questionnaire data used the Racsh mode. The method of the data analysis of this research consisted of three steps: 1) converting the score data of the students into logit data, 2) quantitative description, 3) performing a test analysis by using the t-test. Based on the test t-test, the result of thit is 22,66 with df = (n-1) = (35-1) = 34 with significance level 5%, it is obtained ttable = 1,6909. Based on these results can be concluded that the value of t count> ttable or 22,66> 1,6906. The value of ES = 3.17 then ES is in the high category.The results of this study indicated that there were effects of cognitive behavioral counseling by using social skill technique and problem-solving technique toward self-affiliation of grade X students of SMA Negeri 4 Singaraja.Â Keywords: Cognitive Behavioral CounselingÂ , Rasch, self-affiliation